2008
DOI: 10.1097/01.tp.0000332634.39640.e0
|View full text |Cite
|
Sign up to set email alerts
|

Machine Perfusion Versus Cold Storage in Transplantation of Kidneys From Older Deceased Donors: Results of a Prospective Randomized Multicenter Trial

Abstract: 8 3 MONDAY was similar: 23 6h in CS vs 28 7h in MP (p=NS). in both groups. There were no signifi cant differences between the recipients as to age, gender, duration of ESRD treatment, PRA titres, HLA incompatibility and immunosuppressive treatment. Biopsies were obtained 30 min after reperfusion and snap frozen at 750C. Expression of genes for IL-1b, VEGF, hemoxygenase 1 (HO-1) and hypoxia inducible factor 1 (HIF-1) was analyzed by real-time PCR. Results: Mean Ct for m-RNA expression for HIF-1 in kidney biopsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Twenty-two studies [6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27] identified by the systematic search were included into the analysis (Table 2); fifteen were published papers and seven were abstracts. Ten were RCTs [6,11,12,15,16,18,19,21,24,25], seven studies were retrospective [7,8,9,10,17,22,23], and five were prospective [13,14,20,26,27]. Predominantly, the studies used a LifePort ® kidney transporter for hypothermic machine preservation; there was a large variation in cold storage solution type, with some studies not mentioning the specific cold storage preservation solution, but instead referring to local guidelines.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-two studies [6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27] identified by the systematic search were included into the analysis (Table 2); fifteen were published papers and seven were abstracts. Ten were RCTs [6,11,12,15,16,18,19,21,24,25], seven studies were retrospective [7,8,9,10,17,22,23], and five were prospective [13,14,20,26,27]. Predominantly, the studies used a LifePort ® kidney transporter for hypothermic machine preservation; there was a large variation in cold storage solution type, with some studies not mentioning the specific cold storage preservation solution, but instead referring to local guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies [12,13,15,21,24] which reported PNF (816 patients), demonstrated that HMP significantly decreased primary nonfunction compared to SCS (OR: 0.35 95% CI 1.02 to 2.53, p = 0.003) (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 2203 kidneys were included, 1475 of which were from RCTs and were used in the meta‐analysis ( Table ). Recent European studies have been reported in papers with overlapping populations of patients. Results from these studies were requested from the Scientific Steering Committee so that meta‐analysis could be performed without duplicating patients.…”
Section: Resultsmentioning
confidence: 99%
“…Initial literature searches identified 2619 non‐duplicated references across all databases. Eighteen studies (7 RCTs and 11 non‐RCTs) described in 35 publications met the full inclusion criteria ( Fig . ).…”
Section: Resultsmentioning
confidence: 99%